Endocrine-disruptors compounds in water: a bibliometric perspective - Demonel, Ana Carolina Bazon; Santos, Maria de Fátima Pereira dos; Vicente, Maristela Araújo (Brazilian Journal of Production Engineering, 2022)
The purpose of this article is to investigate the evolution of scientific studies on endocrine-disrupting compounds in water. A bibliometric study was carried out using the Citespace software and the Web of Sience database, from 1945 to 2021. The period with the highest production of articles (2010 to 2021) was chosen with 1624 articles to compose the database. Citespace software was used to analyze the most relevant publications, countries, institutions, authors, and keyword. The results showed that China and the United States contributed with 17, 4% and 16.5% of publications, respectively. Studies on endocrine disrupting compounds in water are multidisciplinary, encompassing ecology from environmental sciences, chemistry, engineering, toxicology, among other fields. Periodicals such as Environmental Science Technology, Chemosphere, Science of the Total Environmental, Water research were the main sources of the cited works. The results showed that the keywords “hormone”, “acid”, “expression” and “metabolite represent emerging trends. We conclude that endocrine-disrupting compounds can represent a challenge and an opportunity to develop methodologies to mitigate these emerging pollutants in freshwater.